Effects of Public Relations Activities on Customer Satisfaction in the University Libraries - Ayşe Gedikçi, Öndoğan (Türk Kütüphaneciliği)
Like all organizations in the process of globalization, university libraries also have focused on their customers much more in order to continue their existence and they have diversified their services in order to increase customer satisfaction. Customer satisfaction emerges as a result of integration of many interdependent components. In this study, public relations works, the most important factor affecting the customer satisfaction, are handled and it is tried to determine the effect of public relations works conducted at Selcuk University Central Library on the customer satisfaction. In the study used descriptive methods, data were obtained from all customer groups who came to the Central Library through questionnaire. It was come out that all customer groups who came to the Central Library were satisfied with public relations works related to the library's physical elements and service elements, but they were not content with public relations works conducted out of the organization in order to improve the customer relations. In consequence of the research, it was observed that the variable that customers gives more importance is the physical elements variable ( =3,86). The most intense relationship between variables is between service element with the physical elements (r=0,667, p<0,01) and public relations elements (r=0,642, p<0,0).